2004
DOI: 10.1089/152308604322899314
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Proliferation Associated with Abrupt Reduction in Shear Stress Is Dependent on Reactive Oxygen Species

Abstract: We have shown previously that flow-adapted endothelial cells respond to cessation of flow with cell membrane depolarization and increased production of reactive oxygen species, resulting in activation of transcription factors and increased DNA synthesis. This study utilized flow cytometry to evaluate cellular proliferation with ischemia and to determine the role of reactive oxygen species and apoptosis. PKH26-labeled rat pulmonary microvascular endothelial cells were seeded in an artificial capillary system an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
55
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 24 publications
10
55
0
Order By: Relevance
“…The response to loss of shear required a preceding period of exposure to flow to reach a flow adapted state. Statically cultured cells kept for short periods under flow did not show any response to stop of flow (5,8,35). Lack or removal of flow in this model did not compromise oxygen delivery to the lung tissues or cells as normal oxygen tension was maintained during stop of flow in vivo (ventilated lung) and in vitro (continuous flow of medium through side ports) (1,5,30,46).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The response to loss of shear required a preceding period of exposure to flow to reach a flow adapted state. Statically cultured cells kept for short periods under flow did not show any response to stop of flow (5,8,35). Lack or removal of flow in this model did not compromise oxygen delivery to the lung tissues or cells as normal oxygen tension was maintained during stop of flow in vivo (ventilated lung) and in vitro (continuous flow of medium through side ports) (1,5,30,46).…”
mentioning
confidence: 80%
“…In general, stop of flow involves 1) compromised oxygen delivery to tissue, and 2) alteration of the mechanical component of blood flow. We established models where stop of flow did not compromise oxygen delivery and nutrient supply; using these models we observed that abrupt cessation of flow causes ROS production via activation of endothelial cell NADPH oxidase (34,35,50). We discovered elements of the cascade, viz.…”
Section: ϫ/ϫmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that the NOX family of enzymes consists of seven widely distributed members (86). The enzyme found in PMN and now called NOX2 also is present in a variety of cell types including microvascular endothelium, where it plays an important role in cellular homeostasis (7,21,25,73,74,115). In our models of altered shear stress, endothelial NADPH oxidase clearly is the source of ROS with ischemia since use of inhibitors of NOX2 activation as well as lungs and cells from NOX2-null mice abolished the effect.…”
Section: Ros Generation: Mechanism For Linkage To Altered Shear Stressmentioning
confidence: 99%
“…3). O 2 ·Ϫ serves as a signal for endothelial cell proliferation, perhaps, teleologically, representing an attempt to restore pulmonary blood flow (62). Thus ROS mediatedsignaling appears to play a key role in the physiological response to altered shear stress associated with lung ischemia (10).…”
Section: Lung Ischemiamentioning
confidence: 99%